Pengembangan Media Pembelajaran Interaktif Berbasis Mobile Bermuatan Problem Based Learning Mata Pelajaran Informatika Pada Kelas X Fase E Di SMA N 1 Koto Balingka - Eti Safitri; Hari Antoni Musril; Sinta Marito (Pusat Riset dan Inovasi Nasional, 2023)
Researchers conducted research at SMA N 1 Koto Balingka which was motivated by the decline in the quality of student learning outcomes. This is due to the lack of learning media facilities in Informatics subjects, such as the lack of development of interesting and effective mobile-based interactive learning media with the Problem Based Learning model in class X phase E at SMA N 1 Koto Balingka, thus making students experience difficulties in understanding the material. lesson . This research aims to design and build Android-based interactive learning media with the theme Problem Based Learning in informatics subjects. This research is field research (field research) which is descriptive qualitative in nature. The key informants in this case are class X students and Informatics teachers at SMA N 1 Koto Balingka. To analyze the data, researchers grouped it based on existing problems.